Sepsis epidemiology and outcome in the paediatric intensive care unit of Vilnius University Children’s Hospital - Bobelytė, Odeta; Gailiūtė, Ieva; Zubka, Vytautas; Žilinskaitė, Virginija (Acta medica Lituanica, 2017)
Research was carried out at the paediatric intensive care unit (paediatric ICU) of the Children’s Hospital, affiliate of Vilnius University Hospital Santariškių klinikos. Background. Being the most common cause of children’s death, sepsis is a challenge for most physicians. In order to improve the outcomes, it is important to know the aetiology and peculiarities of sepsis in a particular region and hospital. The aim of this study was to analyse the outcomes of sepsis in a paediatric intensive care unit and their relation with patients’ characteristics and causative microorganisms. Materials and Methods. A retrospective analysis of the Sepsis Registration System in Vilnius University Children’s hospital was started in 2012. From 2012 to 2015, we found 529 sepsis cases in our hospital, 203 of which were found to be fulfilling all of the inclusion criteria (patient’s age >28 days on admission, taken blood culture/positive PCR test, need for paediatric ICU hospitalization) and were included in the final analysis. Abbreviations: ICD – international disease classification PCR – polymerase chain reaction Results. Sepsis made 4% of all patients of the paediatric ICU in the period from 2012 to 2015 and caused 32% of deaths in the unit. Paediatric mortality reached 14% of all sepsis cases in our analysis, the majority of them due to hospital-acquired sepsis that occurred in patients suffering from oncologic or hematologic diseases. Another significant part of the patients that did not survive were previously healthy with no co-morbidities. The most common microorganism in lethal community-acquired cases was N. meningitidis and in hospital-acquired sepsis – Staphylococcus spp. Multi-drug resistance was observed, especially in the cases of hospital-acquired sepsis. Conclusions. A large percentage of lethal outcomes that occur in the paediatric ICU are due to sepsis. The majority of lethal cases of sepsis occur in patients suffering from chronic co-morbidities, such as oncologic, hematologic, neurologic, and others.